PENGARUH CORPORATE SOCIAL RESPONSIBILITY , UKURAN PERUSAHAAN, STRUKTUR MODAL DAN TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN: Pada Perusahaan Manufaktur Yang Masuk Dalam LQ45 di Bursa Efek Indonesia Periode 2011-2017 - Muhammad Rizal Panggabean (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
The purpose of this study is to examine the effect of Corporate Social Responsibility, Corporate Size, Capital Structure and Tax Avoidance on Firm Value simultaneously and partially. Population in this research is manufacturing company which entered in LQ45 at Indonesia Stock Exchange (BEI) period 2011- 2016. The type of data in this study is secondary data with sample selection technique used is purposive sampling with a period of research for six year. Methods of data analysis in this study is multiple regression analysis with a significance Level of 5 percent. The results showed that simultaneously Corporate Social Responsibility, Company Size, Capital Structure, and Tax Avoidance have a positive and significant effect to Firm Value. Partially, Corporate Social Responsibility has no significant effect on Firm Value, Corporate Size has negative and significant effect to Firm Value, Capital Structure has positive and significant influence to Firm Value, Tax Avoidance has negative and significant effect to Firm Value.